The role of the AR/ER ratio in ER-positive breast cancer patients (2018)
The significance of androgen receptor (AR) in breast cancer (BC) management is not fully defined, and it is still ambiguous how the level of AR expression influences oestrogen receptor-positive (ER+) tumours. The aim of the present study was to analyse the prognostic impact of AR/ER ratio, evaluated by immunohistochemistry (IHC), correlating this value with clinical, pathological and molecular characteristics. We retrospectively selected a cohort of 402 ER+BC patients. On each tumour, IHC analyses for AR, ER, PgR, HER2 and Ki67 were performed and AR+ cases were used to calculate the AR/ER value. A cut-off of >2 was selected using receiver-operating characteristic (ROC) curve analyses. RNA from 19 cases with AR/ER>2 was extracted and used for Prosigna-PAM50 assays. Tumours with AR/ER>2 (6%) showed more frequent metastatic lymph nodes, larger size, higher histological grade and lower PgR levels than cases with AR/ER less than 2. Multivariate analysis confirmed that patients with AR/ER>2 had worse disease-free interval (DFI) and disease-specific survival (DSS) (hazard ratios (HR) = 4.96 for DFI and HR = 8.69 for DSS, both P less than 0.004). According to the Prosigna-PAM50 assay, 63% (12/19) of these cases resulted in intermediate or high risk of recurrence categories. Additionally, although all samples were positive for ER assessed by IHC, the molecular test assigned 47.4% (9/19) of BCs to intrinsic non-luminal subtypes. In conclusion, the AR/ER ratio >2 identifies a subgroup of patients with aggressive biological features and may represent an additional independent marker of worse BC prognosis. Moreover, the Prosigna-PAM50 results indicate that a significant number of cases with AR/ER>2 could be non-luminal tumours. © 2018 Society for Endocrinology Printed in Great Britain Published by Bioscientifica Ltd.